Karakterisasi Peptida Nterm-34 kDa Protein Saliva Nyamuk Aedes aegypti sebagai Kandidat Antigen Biomarker Risiko Transmisi Virus Dengue Secara In Silico - Yunita Armiyanti; Nizar Fiska Bayu Agustian; Sheilla Rachmania (Fakultas Kedokteran Universitas Riau, 2023)
Recently, a new biomarker of mosquito bite has been developed using human antibody response to mosquito salivary protein. One of the proteins that has been tested is salivary protein 34-kDa which has been refined to Nterm-34 kDa peptide. This study aimed to characterize Nterm-34 kDa salivary peptide as a potential antigen biomarker to asses Dengue virus transmission risk. The sequence Nterm-34 kDa was analyzed using several software to predict the characteristic of the peptide. BLASTP from Vectorbase and NCBI wa used to check the specificity of the peptide. IBIVU Praline was used to do multiple sequence alignment. IEDB (Bepipred and Kolaskar & Tongaonkar antigenicity prediction) was used to predict epitopes and antigenic properties, and lastly, ProtParam was used to predict physicochemical properties. The result showed that Nterm-34 kDa salivary peptide is specific to the Aedes aegypti mosquito at the species level and has low conservation compared to other proteins in Aedes aegypti 34-kDa salivary protein family. Nterm-34 kDa is predicted to be antigenic and one of the epitopes. Nterm-34 kDa salivary peptide is predicted to have a molecular weight of 2,092 kDa, unstable, and hydrophilic. In conclusion, Nterm-34 kDa salivary peptide is predicted to have potential as an antigen biomarker for Dengue virus transmission.